The modified taungya system in Ghana’s transitional zone: a win–win practice for forestry and adaptation to climate change? - Kalame, F.B.; Aidoo, R.; Nkem, J.; Ajayi, Oluyede C.; Kanninen, M.; Luukkanen, O.; Idinoba, M. (2011)
The formulation and implementation of an adaptation strategy is of growing concern to governments. The adaptation policy framework (APF) sets out indicative activities and features of an adaptation strategy. Understanding the extent to which existing practices can support adaptation in societies and ecosystems is an important step towards the solution. This study uses vulnerability, policy and financial analyses to investigate the compatibility of the modified taungya system (MTS) (a reforestation programme) in Ghana with the indicative activities of the APF. The findings indicate that MTS takes into consideration most of the activities of an adaptation strategy, is a profitable venture (BCR > 1) and has a high potential to reduce vulnerability due to short-term food production and long-term plantation establishment. Resource management in MTS is promising in the short term, but challenges remain to meet livelihood and adaptation needs in the medium and long term. Policy instruments related to MTS align with the forestry, climate change and the development goals of Ghana. We conclude that MTS is a potential win–win practice for forestry and adaptation. The legalization of all contractual arrangements coupled with continuous monitoring, evaluation and improvement may drive MTS to become a lasting activity that will support the long-term horizon of an adaptation strategy.